A longitudinal study of selected state school aid formula changes in Kansas 1992-2017, with emphasis on the Classroom Learning Assuring Student Success (CLASS) Act of 2015 - Vincent, Shiloh John Daniel (Kansas State University, 2018)
This present study extended the longitudinal perspective begun by DeBacker (2002) and Jordan (2012) and, when considered wholly, provides insights into the educational experiences offered by districts in the state of Kansas from the years 1992 through 2017, as well as the impacts that changes to school funding had on those experiences. This study assessed selected fiscal and pupil performance variables and examined the impacts that changes to school funding had on those variables, paying close attention to the shift from per pupil funding under the School District Finance and Quality Performance Act (SDFQPA) of 1992 to block grant funding under the Classroom Learning Assuring Student Success (CLASS) Act from 2015 to 2017. In the first phase of this study, Kansas school districts were ordered from wealthiest to poorest based on their assessed valuation per pupil for 2001. To narrow the study population and to ensure that longitudinal analysis could occur, districts that had closed or consolidated by 2016 were removed. For the remaining districts, decile analysis was applied to the population by ranking all 289 school districts from wealthiest to poorest based on 2001 assessed valuation per pupil (AVPP) and by further dividing the population in to ten equal parts (i.e. each decile representing 10% of the population). The population was again narrowed to the representative sample of 112 school districts, with Decile 10 representing the wealthiest 10% of districts, Decile 1 representing the poorest 10%, and Deciles 5 and 6 representing the average wealth districts found in the middle (each representing 10% of the population respectively). This process was repeated for 2011, 2014, and 2016. For this study, 2001 and 2016 served as the bookend years, as DeBacker (2002) had done (1992 – 2001) and Jordan (2012) had repeated (2002 – 2012). Establishing the beginning year as 2001 ensured overlap of years examined by both previous studies and extending through the most recent year of audited data, i.e., 2016. Once the study population was established, data analysis was conducted in two phases. First, fiscal and pupil performance data were analyzed to provide insight into overall health of each district during the years 2001- 2016. Second, survey and interview data were collected and analyzed to glean insights from district leaders for contextual perspective of the impacts that changes to school funding had on districts and their leaders, paying close attention to the years of block grant funding under CLASS. The present study resulted in a critical examination of fiscal and pupil performance variables and the impact that changes to school finance in Kansas had on the educational experience of Kansas pupils.
Keywords: Educational leadership; School finance; Classroom Learning Assuring Student Success (CLASS) Act; School District Finance and Quality Performance Act (SDFQPA); Kansas school funding; K-12 Education